EKSISTENSI TRADISI MANYANDA PADA KEHIDUPAN SOSIAL MASYARAKAT DI NAGARI TALANG, KAB. SOLOK, SUMATERA BARAT - Efri Yolanda (UIN Imam Bonjol Padang, 2020)
The development of traditional to modern society has had a major influence on the social and cultural life of the community. Shifting or even disappearance of a culture in society becomes an effect of the times. But on the other hand, the people of Nagari Talang still preserve the manyanda tradition at the death ceremony even though there have been some shifts. This tradition has its own uniqueness, it can be seen in the name of manyanda tradition, the procession, and its role in people's lives. So, why does this tradition still exist, even though several other cultures have been lost because of the age. Then this study aims to describe the existence of manyanda traditions that are still valid today. Sources were obtained through in-depth interviews and field research to explore accurate information. In addition, secondary sources were obtained from the Bundo Kanduang record of the 2018 death custom, the Wali Nagari Talang Office, and the library. The results showed that this tradition has become an identity and need for the community because it has a positive impact on the social life of the community, so that it still exists and is preserved by the community.